Capitalism, Communism and Confucius? Some Reflections on Asian Grwth and Crisis - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2001)
The economic development in East and Southeast Asia after 1960 is discussed in light of economic growth theory', international security politics, and Asian culture. It is argued that the East Asian growth miracle became possible partly due to very favorable combination of factors along these three dimensions. The initial growth potential was high, while the stability requiredfor growth to materialize was encouraged by the international political s ituation, and possibly also by cultural characteristics of the region. The economic crisis in 1997 need not represent the end of long run growth as far as growth theory can predict, but nor does the risk of political set-backs that could have negative growth effects seem to be lower than before.